Spreading profile of evaporative liquid drops in thin porous layer - Chong, W.Y.; Lim, K.S.; Lim, W.H.; Harun, Sulaiman Wadi; Adikan, Faisal Rafiq Mahamd; Ahmad, Harith (2012)
Spreading of evaporative liquid drops in a thin porous layer has been studied. The entire spreading process can be divided into three distinct phases according to the change of the wetted porous region size. The first phase is characterized by the expansion of the wetted porous region and shrinking of the liquid drop. Contact line pinning is observed in the wetted porous region in the second phase even with the liquid drop totally absorbed into the porous layer. The third phase sees the shrinkage of the wetted porous region until it is not observable. Based on these observations, a model is devised to simulate the spreading of a liquid drop under the studied conditions. Partial differential equations are used to describe the relation between liquid drop volume and other important parameters of a fluid flow, including maximum wetted region diameter achieved, time taken to reach each spreading process phase, and evaporation rate. Calculated results are in good agreement with the experimental data.